Dealing with meetings you can't stand : meet less and do more - Brinkman, Rick (McGraw Hill-Ascent Audio, 2017)
The proven process for making the most of every business meeting-from the coauthor of the international bestseller Dealing with People You Can't Stand From Dr. Rick Brinkman, one of the bestselling masterminds who made Dealing with People You Can't Stand a little less painful-and a lot more productive-comes the much-needed cure for that time-wasting, headache-inducing, soul-sucking plague known as meetings. This proven step-by-step method addresses the most common problems that derail a meeting: preparation, people, process, and time. Dr. Brinkman provides key insights into the human behaviors that lead to unsuccessful meetings, along with psychologically-based tactics for addressing them. You will learn how to: * get rid of unnecessary meetings * start and end on time * develop and execute an effective agenda * address disruptive and problem behaviors * balance participation so assertive people don't dominate and passive people say what they really think * eliminate tangents and maintain focus * ensure effective follow-up This practical and easily implementable process applies to in-person as well as virtual meetings of any size. Filled with helpful checklists and change-making strategies, Dealing with Meetings You Can't Stand will turn the most boring conference room into a fast-moving model of efficiency, energy, and enthusiasm. You need not suffer in a meeting ever again.